The Effect of Cafe Atmosphere and Food Quality on Revisit Intention with Customer Satisfaction as a Mediating Variable at Cafe in Medan City - Cendikia Taqwim; Bunga Aditi; Sopi Pentana (Jurnal Ekonomi LLDIKTI Wilayah 1 (JUKET), 2021)
This study aims to determine whether the cafe atmosphere and food quality affect revisit intention with customer satisfaction as a mediating variable at cafes in Medan. The analytical technique used is path analysis as an analytical tool to determine the direction of the variables studied and justify how significant the influence of the independent variable with the dependent variable is either directly or indirectly through the mediating variable. The total population in this study amounted to 112 people, and 112 were used as samples using the saturated sampling method, namely the model, which also represented the total population. The results showed that cafe atmosphere had a significant effect on customer satisfaction, food quality had a significant effect on customer satisfaction, cafe atmosphere had a significant effect on revisit intention, food quality had a significant effect on revisit intention, customer satisfaction had a significant effect on revisit intention, cafe atmosphere and food quality had a significant effect on customer satisfaction, cafe atmosphere and food quality have a significant effect on revisit intention, cafe atmosphere has a significant effect on revisit intention through customer satisfaction, and food quality has a considerable effect on revisit intention through customer satisfaction.